Continuous biohydrogen production by a degenerated strain of Clostridium acetobutylicum ATCC 824 - Guerrero, Karlo; Gallardo Marusich, Roberto Andres; Paredes, Ivan; Quintero, Julian; Mau, Silvia; Conejeros, Raul; Carlos Gentina, Juan; Aroca, German (My University, 2021)
Degenerated strains of Clostridium acetobutylicum lack the ability to produce solvents and to sporulate, allowing the continuous production of hydrogen and organic acids. A degenerated strain of Clostridium acetobutylicum was obtained through successive batch cultures. Its kinetic characterization showed a similar specific growth rate than the wild type (0.25 h(-1)), a higher butyric acid production of 6.8 g-L-1 and no solvents production. A steady state was reached in a continuous culture at a dilution rate of 0.1 h(-1), with a constant hydrogen production of 507 mL.h(-1), corresponding to a volumetric rate of 6.10 L.L(-1)d(-1), and a yield of 2.39 mol of H-2 per mole of glucose which represents 60% of the theoretical maximum yield. These results suggest that the degeneration is an interesting alternative for hydrogen production with this strain, obtaining a high hydrogen production in a continuous culture with cells in a permanent acidogenic state. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: clostridium acetobutylicum; degenerated strain; biohydrogen; dark fermentation; hydrogen production